Real-world analysis of survival outcomes in advanced EGFR-mutant NSCLC patients treated with platinum-pemetrexed after EGFR-TKI treatment failure - Zong-Han Yao; Wei-Yu Liao; Chin-Yao Yang; Chao-Chi Ho; Jin-Yuan Shih; Kuan-Yu Chen; James Chih-Hsin Yang; Chong-Jen Yu (Journal of the Formosan Medical Association)
Introduction: EGFR tyrosine kinase inhibitors (TKIs) are the standard therapy for non-small-cell lung cancer (NSCLC) patients with EGFR-activating mutations in the first-line setting. Despite initial efficacy, resistance to EGFR-TKIs often develops, and platinum-based chemotherapy is the predominant subsequent treatment. For this study, we aimed to identify prognostic factors for overall survival (OS) and progression-free survival (PFS) among advanced EGFR-mutant NSCLC patients receiving platinum-pemetrexed after progression on EGFR-TKIs. Our analysis specifically focuses on 1st-line treatments limited to 1st- or 2nd-generation EGFR-TKIs, while not restricting later-line treatments involving osimertinib prior to chemotherapy. Materials and methods: From 2012 to 2017, 363 patients who received first-line treatment with first- or second-generation EGFR-TKIs, including gefitinib, erlotinib, and afatinib were enrolled. Some patients received different EGFR-TKIs, including osimertinib, as later-line treatment before platinum-pemetrexed. Results: Median OS from the initiation of platinum-pemetrexed was 22.0 months and median PFS with platinum-pemetrexed was 6.2 months. In the multivariate Cox model, we identified three independent prognostic factors for better OS: postoperative recurrence (HR: 0.34, p = 0.004), first-line EGFR-TKI PFS ≥12 months (HR: 0.54, p = 0.002), and osimertinib treatment after platinum-pemetrexed (HR: 0.56, p = 0.005) while BMI <18.5 indicated poor prognosis (HR:1.76, p = 0.049). No statistically significant independent prognostic factors for PFS were found. Receiving osimertinib before platinum-pemetrexed treatment did not impact PFS with platinum-pemetrexed treatment (HR: 1.11, p = 0.64). Conclusion: Postoperative recurrence, first-line EGFR-TKI PFS ≥12 months and osimertinib treatment after platinum-pemetrexed predicted better OS, while BMI <18.5 predicted worse OS. Osimertinib treatment before platinum-pemetrexed treatment did not affect the efficacy of platinum-pemetrexed.